How Does PT Surya Sembada Integrate Corporate Social Responsibility into Its PR Strategy? - Lisdiantini, Netty; Mulyadi, Edi; Mashudi; Fauziah, Luluk Fauziah; Brumadyadisty, Garry (PT. Banjarese Pacific Indonesia, 2024)
This study explores the important role of public relations (PR) in shaping and maintaining PT Surya Sembada's corporate reputation. As a cornerstone of organizational success, reputation serves as a critical asset in a competitive business landscape. The research utilizes a comprehensive approach of qualitative methods to assess the multifaceted dimensions of the PR strategy implemented by PT Surya Sembada. The investigation begins by examining the theoretical underpinnings of corporate reputation and the evolving landscape of PR practice in the contemporary business environment. It then delves into case-specific analysis, evaluating the effectiveness of PT Surya Sembada's PR initiatives in enhancing brand image, fostering stakeholder relationships, and mitigating potential crises. Key findings highlight the strategic alignment between PR efforts and corporate objectives, emphasizing the role of transparent communication in fostering trust among stakeholders. The study also underscores the impact of digital platforms and social media in shaping public perception, requiring proficient management by PR practitioners. In addition, this research highlights the challenges faced by PT Surya Sembada in maintaining a positive reputation amidst dynamic market conditions. It offers actionable insights to refine PR strategies, emphasizing the importance of adaptability and proactive communication to navigate unexpected challenges. This analysis enhances the understanding of the symbiotic relationship between PR and corporate reputation, offering practical recommendations for PT Surya Sembada and other companies to enhance their reputational resilience in the current business environment.